Untangling the paradoxical relationship between religion and business: a systematic literature review of chief executive officer (CEO) religiosity research - Heubeck, Tim (Journal of business ethics, 2024)
Despite numerous chief executive officers (CEOs) citing their religious convictions as the primary guiding framework for their decision-making, leadership behavior, business philosophy, and motivation to contribute to society, the impact of CEOs’ religious convictions is relatively limited in the business literature. However, the widespread yet potentially ambiguous impact of CEO religiosity, encompassing both a CEO’s religious denomination and level of religiosity, on individual, organizational, economical, and societal levels remains a neglected area of research. This gap is attributed to challenges in conceptualizing and measuring this multifaceted construct, with existing research scattered and predominantly confined to the ethics domain. Notably, this oversight is significant given the pivotal role that CEOs, as primary decision-makers, play in organizational dynamics. This article aims to address this gap by conducting a systematic literature review of 50 articles focused on CEO religiosity, seeking to enhance the understanding of personal religion in the business world. Through an analysis of publication trends, methodological approaches, theoretical frameworks, and empirical findings, the review not only offers insights for future research and theorizing but also proposes a conceptual framework for understanding and advancing CEO religiosity research. Additionally, this review identifies specific areas warranting further investigation, thereby highlighting existing research gaps and providing explicit starting points for future research. Through these contributions, this article provides a blueprint for future research on CEO religiosity and holds significant implications for management practice.